Thyroid hormone induces DNA demethylation in Xenopus tadpole brain - Denver, Robert; Raj, Samhitha; Kyono, Yasuhiro; Sifuentes, Christopher; del Carmen Arellanes-Licea, Elvira; Subramani, Arasakumar (Dryad, 2020)
Thyroid hormone (T3) plays pivotal roles in vertebrate development, acting
via nuclear receptors (TRs) that regulate gene transcription by promoting
posttranslational modifications to histones. Methylation of cytosine
residues in DNA also modulates gene transcription, and our recent finding
of predominant DNA demethylation in the brain of Xenopus tadpoles at
metamorphosis, a T3-dependent developmental process, caused us to
hypothesize that T3 induces these changes in vivo. Treatment of
pre-metamorphic tadpoles with T3 for 24 or 48 hr increased
immunoreactivity in several brain regions for the DNA demethylation
intermediates 5-hydroxymethylcytosine (5-hmC) and 5-carboxylcytosine, and
the methylcytosine dioxygenase ten-eleven translocation 3 (TET3). Thyroid
hormone treatment induced locus-specific DNA demethylation in proximity to
known T3 response elements within the DNA methyltransferase 3a and
Krüppel-like factor 9 genes, analyzed by 5-hmC immunoprecipitation and
methylation sensitive restriction enzyme digest.
Chromatin-immunoprecipitation (ChIP) assay showed that T3 induced TET3
recruitment to these loci. Furthermore, the mRNAs for several genes
encoding DNA demethylation enzymes were induced by T3 in a time-dependent
manner in tadpole brain. A TR ChIP-sequencing experiment identified
putative TR binding sites at several of these genes, and we provide
multiple lines of evidence to support that tet2 contains a bona fide T3
response element. Our findings show that T3 can promote DNA demethylation
in developing tadpole brain, in part by promoting TET3 recruitment to
discrete genomic regions, and by inducing genes that encode DNA
demethylation enzymes.
Keywords: Thyroid; Xenopus; Metamorphosis; DNA methylation; Chromatin; Brain development